Reduction in insulin degludec dosing for multiple exercise sessions improves time spent in euglycaemia in people with type 1 diabetes: A randomized crossover trial - Moser, Othmar (Diabetes Obes Metab, 2018)
AIMS: To compare the time spent in specified glycaemic ranges in people with type 1 diabetes (T1D) during 5 consecutive days of moderate‐intensity exercise while on either 100% or 75% of their usual insulin degludec (IDeg) dose. MATERIALS AND METHODS: Nine participants with T1D (four women, mean age 32.1 ± 9.0 years, body mass index 25.5 ± 3.8 kg/m(2), glycated haemoglobin 55 ± 7 mmol/mol (7.2% ± 0.6%) on IDeg were enrolled in the trial. Three days before the first exercise period, participants were randomized to either 100% or 75% of their usual IDeg dose. Participants exercised on a cycle ergometer for 55 minutes at a moderate intensity for 5 consecutive days. After a 4‐week wash‐out period, participants performed the last exercise period for 5 consecutive days with the alternate IDeg dose. Time spent in specified glycaemic ranges, area under the curve and numbers of hypoglycaemic events were compared for the 5 days on each treatment allocation using a paired Students' t test, Wilcoxon matched‐pairs signed‐rank test and two‐way ANOVA. RESULTS: Time spent in euglycaemia over 5 days was greater for the 75% IDeg dose versus the 100% IDeg dose (4008 ± 938 minutes vs. 3566 ± 856 minutes; P = 0.04). Numbers of hypoglycaemic events (P = 0.91) and time spent in hypoglycaemia (P = 0.07) or hyperglycaemia (P = 0.38) was similar for both dosing schemes. CONCLUSIONS: A 25% reduction in usual IDeg dose around regular exercise led to more time spent in euglycaemia, with small effects on time spent in hypo‐ and hyperglycaemia.